Peningkatan Prestasi Belajar Siswa pada Materi Kesebangunan dan Kekongruenan Melalui Pendekatan Saintifik di Kelas IX A SMP Negeri 2 Arut Selatan Tahun Pelajaran 2020/2021: Improving Student Achievement in Congruence and Congruence Materials Through a Scientific Approach in Class IX A SMP Negeri 2 Arut Selatan Academic Year 2020/2021 - Sibarani, Lisma (Anterior Jurnal, 2022)
In the pre-cycle, the number of students who completed learning reached 7 students. The average value has only reached 68, which means it is still below the KKM. The results of the observations showed a score of 39. This means that the activity of students in the class is not good. In the first cycle, the number of students who completed learning reached 19 students, the average value reached 78. This means that an effective scientific approach is used to improve student achievement in the material of similarity and congruence. In student observation activities, the teacher assesses that students listen to the material conveyed by the teacher, students look enthusiastic in participating in Mathematics learning material congruence and congruence, students can express their opinions, students ask questions about things they don't know and students can work in groups with other friends. The results of the observations showed a score of 85. It means that the activity of students in the class is quite good. However, in order to make it more conducive to learning Mathematics in terms of similarity and congruence, the researcher wants to carry out cycle II. In the second cycle, the number of students who completed learning reached 24 students, the average score was 85. This means that an effective scientific approach is used to improve student achievement in the material of similarity and congruence. Observation results show a score of 108. It means that the activity of students in the class is very good.